DIAGNOSTIC AND DESCRIPTION OF ASIAN PANGASIID CATFISH GENUS Helicophagus FROM SOUTHEAST ASIA - Rudhy Gustiano; Muhammad Hunaina Fariduddin Ath-thar; Vitas Atmadi Prakoso; Deni Radona; Irin Iriana Kusmini (Research Center for Fisheries, 2019)
Pangasiid catfishes is an economic important catfish family for fishery. Nowadays, three species, Pangasius hypophtahlmus, P. boucorti, and P. djambal, are used in aquaculture. Among the genera in Pangasiidae, Helicophagus was less studied. Although this genus was less preferred than other popular species in Pangasiidae, it still has high commercial price. The present study was conducted to clarify the differences of the exist species in the genus Helicophagus based on biometric analyses. Twenty six specimens, collected from represent rivers in Southeast Asia, used for the material examined. Several type specimens deposited in museums were also added in the analyses. Thirty five characters were designed for measurement on the unique body conformation. Principal component analysis (PCA) was applied to distinguish different species and found strong characters for key identification and description. The results presented the data and information on the diagnosis, description, distribution, and ecology of each species. Key identification of each species are given. The three species (Helicophagus typus, H. waandersii, and H. leptorhynchus) enabled to show their differences based on eye diameter and vomerine toothplate length.